Polymorph II of hydroxyurea 150 years after its first synthesis - Rai, Sunil K.; Tothadi, Srinu; Arhangelskis, Mihails; George, Christy P.; Gonnade, Rajesh G.; Nangia, Ashwini K. (Crystengcomm, 2023)
A new polymorph of hydroxyurea (HU) was crystallized 150 years after its first synthesis. Due to its medicinal use in neoplastic diseases and sickle cell anemia, a high throughput screen of HU binary cocrystals was attempted. Instead of a cocrystal, an isoenergetic form II crystallized concomitantly with urea in methanol.